Land use patterns and types of common vole (Microtus arvalis) population kinetics - Delattre, Pierre; Giraudoux, Patrick; Baudry, Jacques; Musard, P.; Toussaint, M.; Truchetet, D.; Stahl, P.; Poule, M.L.; Artois, M.; Damange, J.P.; Quéré, J.P. (HAL CCSD, 1992)
International audience